Beauty and the Beast (Parrogon Books Ltd, 2014)
Belle dreams of leaving her small-town life, but she gets more than she bargains for when she becomes imprisoned in an enchanted castle with the mysterious Beast! Will she learn to love him and break the curse before it's too late?...
Keywords: Fairytales